2021
DOI: 10.1002/jeq2.20255
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic trade‐offs of using composted or stockpiled manure as partial substitute for synthetic fertilizer

Abstract: Manure generated from livestock production could represent an important source of plant nutrients in substitution of synthetic fertilizer. To evaluate the sustainability of partially substituting synthetic fertilizer with soil organic amendments (OA) in horticulture, an economic and greenhouse gas (GHG) budget was developed. The boundary for analysis included manure processing (stockpiling versus composting), transport and spreading of manure and compost (feedlot and chicken) in intensively cultivated horticul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Most of the farms do not have a corresponding fecal treatment system, especially those small farmers who choose the way of stocking for breeding. Animal waste is an important source of AGNPS pollution, its output is huge and pollution is widespread, but the corresponding pollution prevention countermeasures are relatively weak [78]. The discharge of livestock and poultry feces is large and highly random, then the direct or indirect discharge of eutrophic substances such as nitrogen and phosphorus into the water bodies, causing serious pollution to water quality [79].…”
Section: Pollution Of Livestock and Poultry Breedingmentioning
confidence: 99%
“…Most of the farms do not have a corresponding fecal treatment system, especially those small farmers who choose the way of stocking for breeding. Animal waste is an important source of AGNPS pollution, its output is huge and pollution is widespread, but the corresponding pollution prevention countermeasures are relatively weak [78]. The discharge of livestock and poultry feces is large and highly random, then the direct or indirect discharge of eutrophic substances such as nitrogen and phosphorus into the water bodies, causing serious pollution to water quality [79].…”
Section: Pollution Of Livestock and Poultry Breedingmentioning
confidence: 99%
“…In a study of the environmental outcomes of substituting manure products for commercial fertilizers, De Rosa et al. (2022) compared composted and stockpiled manure as a substitute for commercial fertilizer. They found that a program of composted manure and judicious N fertilizer use resulted in 9–90% less greenhouse gas emissions than one relying upon unprocessed, stockpiled manure.…”
Section: Dimensions Of the Manureshedmentioning
confidence: 99%
“…Utilization of dairy manure as a nutrient source for agricultural production is a potential way to sustainably use dairy waste products (De Rosa et al, 2022). However, the application of raw dairy manure to agricultural fields often leads to nitrogen (N) and phosphorus (P) leaching that threatens water quality (Cao and Harris, 2010;Ghezzehei et al, 2014;Pagliari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Manures are typically applied to soils at rates needed to meet plant N requirements, thus exceeding P requirements by up to six times (Carey et al, 2011), which may lead to legacy P accumulation in the soil (McDowell and Sharpley, 2001). Due to the widespread threat from dairies to surface water quality (US EPA, 2013;Femeena et al, 2023), there is a major imperative to develop nutrient recycling technology from dairy waste that will reduce nutrient leaching and improve the dairy bioeconomy, soil health, and nutrient resource sustainability (Adhikari et al, 2005;Van Zanten et al, 2019;Bach et al, 2021;Muscat et al, 2021;De Rosa et al, 2022). Meeting this imperative requires research to develop technology to recover P and N from dairy waste and test its efficacy as a beneficial soil amendment (Kushwaha et al, 2011;Kolev, 2017;Ahmad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%